2022
DOI: 10.1099/mic.0.001154
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial pore-forming toxins

Abstract: Pore-forming toxins (PFTs) are widely distributed in both Gram-negative and Gram-positive bacteria. PFTs can act as virulence factors that bacteria utilise in dissemination and host colonisation or, alternatively, they can be employed to compete with rival microbes in polymicrobial niches. PFTs transition from a soluble form to become membrane-embedded by undergoing large conformational changes. Once inserted, they perforate the membrane, causing uncontrolled efflux of ions and/or nutrients and dissipating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 249 publications
(537 reference statements)
0
25
0
4
Order By: Relevance
“…The fundamental step of pore formation consists of binding of toxin protomers to a receptor (lipids, glycans or proteins) on the surface of the target cell membrane. Receptors increase the local concentration of the toxin and also promote oligomerization [ 76 ]. As was also demonstrated previously, flavonoids could interact with phospholipid and protein components of erythrocyte membranes and protect erythrocytes against hypotonic lysis [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fundamental step of pore formation consists of binding of toxin protomers to a receptor (lipids, glycans or proteins) on the surface of the target cell membrane. Receptors increase the local concentration of the toxin and also promote oligomerization [ 76 ]. As was also demonstrated previously, flavonoids could interact with phospholipid and protein components of erythrocyte membranes and protect erythrocytes against hypotonic lysis [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Time‐resolved studies of VapA binding and intercalation using a biosensor and film balance revealed a significant decrease in membrane fluidity and limited intercalation of VapA. To spatially visualize the interaction positions of VapA on model membranes and to determine whether VapA, like other bacterial pore formers, organizes into oligomeric structures on or in the membrane (Ulhuq & Mariano, 2022; Yamashita et al., 2014), we use atomic force microscopy (AFM), which allows imaging of surfaces in air and in liquid with nanometer spatial resolution. First, solid‐supported monolayers were prepared by single Langmuir–Blodgett transfer and examined by AFM.…”
Section: Resultsmentioning
confidence: 99%
“…4d ), suggesting potential molecular differences between mechanisms of T6SS induction by polymyxin B versus by PSMs treatment. Polymyxin B can be inserted into the membrane, causing cell lysis by creating pores in the envelope 34 . In contrast, PSMs are cationic, amphipathic small helical peptides with membrane perturbing and cell surface-adhering properties 35 .…”
Section: Resultsmentioning
confidence: 99%